Using Deep Learning to Identify High-Risk Patients with Heart Failure with Reduced Ejection Fraction - Zhibo Wang; Xin Chen; Xi Tan; Lingfeng Yang; Kartik Kannapur; Justin L. Vincent; Garin N. Kessler; Boshu Ru; Mei Yang (Journal of Health Economics and Outcomes Research)
**Background:** Deep Learning (DL) has not been well-established as a method to identify high-risk patients among patients with heart failure (HF).